If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(1 + -2x) + -5 = -83 (1 * 6 + -2x * 6) + -5 = -83 (6 + -12x) + -5 = -83 Reorder the terms: 6 + -5 + -12x = -83 Combine like terms: 6 + -5 = 1 1 + -12x = -83 Solving 1 + -12x = -83 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -12x = -83 + -1 Combine like terms: 1 + -1 = 0 0 + -12x = -83 + -1 -12x = -83 + -1 Combine like terms: -83 + -1 = -84 -12x = -84 Divide each side by '-12'. x = 7 Simplifying x = 7
| 24x^2+2xr-r^2=0 | | 2x^3+x^2-19x+36=y | | -[2]=x-9 | | -2(v+3)=-18 | | x^2+1.68=2.6x | | 5(-4+m)=-45 | | 2x^3+x^2-19x+36=x | | -5r-3=-33 | | 6(4x+7)=105 | | 5(n+5)=34+8n | | f(x)=2x^3+x^2-19x+36 | | 3(x+2.5)=-7.5 | | x+6-2x-4=0 | | 9+3(2x-6)=14 | | -54=9n | | 6n-12=150 | | 3(x+2.5)=7.5 | | 4+2(a+4)=-20 | | 9x-6=2x+8 | | 4x+2(3x-6)=4 | | y=-2x-17 | | 2y+3=31 | | a+3+20=-1+3a+4 | | -10x=5x-1 | | 3=3x+3 | | 4d=-2(33+d) | | 1=3x+3 | | -1=3x+3 | | 10(-2)=-20 | | -5=3x+3 | | -2[-3x-8]=w | | m+2m-6=-12 |